Mediatization and circulation: - Eckhardt, Andreia Primaz (Anais de Artigos do Seminário Internacional de Pesquisas em Midiatização e Processos Sociais; Vol 1 No 6 (2024): Anais de Artigos do VI Seminário Internacional de Pesquisas em Midiatização e Processos Sociais - Anthropocene, classifications and environment: perspectives from mediatization, 2024)
This article marks the starting point of the author's dissertation and offers a theoretical reflection on the concepts that will guide the final work of the Master's in Communication. In this work, we will explore some concepts related to a mediatized society from the perspective of Latin American authors. Additionally, we will briefly address the context of the dissertation's object: the final televised debate of the 2022 elections held in Brazil.